High Load of Deformed Wing Virus and Varroa destructor Infestation Are Related to Weakness of Honey Bee Colonies in Southern Spain - Barroso-Arévalo, Sandra; Fernández-Carrión, Eduardo; Goyache, Joaquín; Molero, Fernando; Puerta, Francisco; Sánchez-Vizcaíno, José Manuel (Frontiers in Microbiology, 2019)
Many factors, including pathogens, contribute to the continuing losses of colonies of the honey bee Apis mellifera, which has led to steady population decline. In particular, colony losses have been linked to deformed wing virus (DWV) and the Varroa destructor mite. To clarify the potential role of these two pathogens in honey bee colony weakening and loss, we sampled colonies in southern Spain during a 21-month period and analysed the samples for loads of four viruses and varroa. Loads of DWV and black queen cell virus as well as varroa infestation negatively correlated with colony vigour as measured using the subjective colony strength method. Logistic regression identified varroa and DWV as the main factors involved in colony weakening. Our results confirm that varroa and DWV play a key role in triggering colony weakening in southern Spain, and provide evidence that experienced beekeepers' and Technicians’ assessments of colony vigour can accurately estimate colony strength.